Media Sosial dalam Membangun Opini Publik atas Layanan Pemerintah: Kajian Literatur Interaksi Sosial Digital - Tamba, Dumanita; Kholikin, Rafi Akhsanul (Universitas Airlangga, 2025)
This study aims to understand the role of social media in building public opinion on government services by highlighting how digital social interactions affect public legitimacy and trust. The main focus of this research is directed at the question of how social media functions not only as a means of communication, but also as a deliberative space that strengthens citizen participation. This research uses a descriptive qualitative approach through a literature study, by analyzing the latest academic literature in the last five years that is relevant to the themes of digital participation, public opinion, and e-governance. Data were obtained from reputable journals, research reports, and policy documents, and then analyzed thematically to identify key themes, patterns, and trends that emerged in previous studies. The results of the analysis show that social media contributes to strengthening participatory democratic practices by providing a space for the public to express their aspirations, criticism, and support for the government. The study also highlights the need for more empirical follow-up research, particularly related to the influence of social media algorithms and citizens' subjective experiences. Keywords: Social Media, Public Opinion, Government Services, Digital Participation, E-governance